Behavior of Composite Beam with Partial ConnectionUnder Flexural Wave Propagation - Abd AL-Latef Numan, Hesham (Journal of Engineering and Sustainable Development, 2008)
This research presents a theoretical study to the behavior of composite beam with partial connection under flexural wave propagation, connected together by stud shear connectors. Equilibrium and compatibility are satisfied for the forces and displacements at the assumed element. As a result, five simultaneous differential equations with respect to x-axis and time (t), with different deflections and rotations in each element, taking into account slip occurring at the interface between elements, and entire effect of time by the method of characteristics with Laxwendroff solution. A computer program is written in (Visual Basic) to apply the suggested theoretical model.